The Separate Removal of Trace CO and Moist NO from Off-Gases by Adsorption on H-Type Mordenite - Z.-M. Wang; T. Arai; M. Kumagai (Adsorption Science & Technology)
Three kinds of mordenite were examined for the adsorptive separation and removal of trace amounts of 14 CO 2 and moist NO x contained in the off-gases of reprocessing plants for spent nuclear fuels. It was found that protonation of mordenite eliminated any possible removal of CO 2 by specific adsorption but induced the dissociative adsorption of NO 2 with the formation of nitric acid-like adsorbed species and NO oxidation. FT-IR spectroscopic results confirmed that the Brönsted acid sites existing on H-type mordenites exhibit no interaction with CO 2 molecules but can catalyze the dissociative adsorption of NO 2 . Such properties, together with the lower adsorption temperature and the thermal stability of the adsorbent, suggest a promising process involving H-type mordenites whereby NO x can be selectively captured and returned to the dissolving solution while trace amounts of 14 CO 2 -containing carbon oxides pass through the system allowing their subsequent complete removal by entrapment in a solid matrix.